8. ORGANISING DIVERSE RURAL COMMUNITIES INTO FUNCTIONAL GROUPS IN INDONESIA: THE GAP BETWEEN THEORY, POLICY AND PRACTICE - Muktasam Muktasam (JURNAL AGRIMANSION, 2003)
ABSTRACT Since Mass Guidance (Bimas) in the 1960s, it was realised that community organising is the way to achieve rural development. The focus of this paper is to discuss how community organisations played their roles and what factors contributed to their performance. A longitudinal study using Modified Parti-cipatory Action Research was conducted in West Lombok-Indonesia. The study found that even though the policies on groups are theoretically sound, most groups failed to perform their expected roles and few succeeded. The agency practices used in esta-blishing groups were focused on projects, in a top-down and rushed approach. Field staff support and training of personnel are needed to translate the policies from rhetoric to reality. Another lesson learned from this study is that formation of functional groups should take into account the existence of diversity within the community and agencies. ABSTRAK Sejak dilaksanakannya Bimas, pemerintah menyadari bahwa mengelompokkan masyarakat kedalam kelompok-kelompok fungsional menjadi salah satu cara dalam membangun masyarakat pedesaan. Fokus dari tulisan ini adalah mengkaji bagaimana kelompok-kelompok fungsional memainkan perannya dalam pembangunan dan faktor-faktor apa yang mempengaruhi kinerja kelompok. Studi longitudinal ini dilaksanakan di Lombok Barat-Indonesia dengan menggunakan metode Modified Participatory Action Research (MPAR). Hasil penelitian menunjukkan bahwa sebagian besar kelompok gagal memainkan perannya sebagaimana diharapkan. Upaya pembentukan kelompok lebih difokuskan pada pendekatan “proyek”, “top-down” dan “terburu-buru”. Dukungan dan pelatihan bagi petugas lapangan diperlukan dalam rangka menterjemahkan kebijakan dari sekedar “diomongkan” menjadi “realitas” sosial. Pelajaran lain yang diambil dari kajian ini adalah bahwa proses pembentukan kelompok-kelompok fungsional seharusnya memperhatikan kemajemukan masyarakat serta lembaga yang terlibat dalam proses pembangunan.